Analyzing the effect of yarn and fabrics parameters on electromagnetic shielding of metalized fabrics coated with polyaniline. (November 2014) - Manesh, Fatemeh Yousefi; Hasani, Hossein; Mortazavi, Sayed Majid
In this article, the effect of various yarn and fabric parameters on the electromagnetic shielding of metalized fabrics coated with polyaniline has been investigated. Copper wires with diameters of 0.06, 0.08 and 0.1 mm were chosen as conductive ﬁllers for producing the metalized core-spun yarn. To investigate the effect of sheath material, cotton, viscose and polyester fibers supplied in a roving form were used to produce different core-spun yarn on a ring spinning frame. From the produced core yarn, woven fabrics were produced in three different pick densities: 12, 16 and 20 picks per cm. Polyaniline was synthesized in two chemical polymerization methods to achieve different surface conductivity. Taguchi's experimental design was used to estimate the optimum process conditions and to examine the individual effects of each of the controllable factors on a particular response. The fabric parameters considered in this article were: copper wire thickness, sheath material type, fabric pick density and the coating compound chemical polymerization method. The electromagnetic effectiveness was measured at the frequency range of 1.7–2.7 GHz, using a waveguide. According to the level average analysis, fabric density factor shows the strongest effect on electromagnetic shielding, factor thickness of copper wire is the second and is followed by the factor coating compound chemical polymerization method and the sheath material type. The findings revealed that the samples at the frequency range 2.4–2.45 GHz show the highest shielding.